2017
DOI: 10.1515/nbec-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Acinetobacter spp. adapted to heavy metal polluted environments

Abstract: Multiple metallotolerant bacterial strains were isolated from soil and drainage water samples collected from three industrially heavy metals polluted areas in Slovakia. Obtained bacterial isolates were identified using MALDI-TOF mass spectrometry and bacterial isolates that belonged to the Acinetobacter genus were subjected for the further study. A. calcoaceticus was found to be prevalent species among analyzed Acinetobacter spp. strains, followed by A. lwoffii and A. johnsonii. A. calcoaceticus strains exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…The genomic DNAs of the P. aeruginosa clinical isolates were extracted by alkaline lysis method using Sodium Dodecyl Sulfate (SDS) and NaOH. 12 First, 3-5 colonies of the overnight grown bacteria were suspended in 60 μL of an alkaline solvent (0.5 gr SDS and 0.4 gr NaOH dissolved in 200 μL distilled water), then warmed at 95°C for 10 minutes. Next, centrifuged at 13000 rpm for 5 min, and 180 μL distilled water added to the mixture.…”
Section: Genomic Dna Extractionmentioning
confidence: 99%
“…The genomic DNAs of the P. aeruginosa clinical isolates were extracted by alkaline lysis method using Sodium Dodecyl Sulfate (SDS) and NaOH. 12 First, 3-5 colonies of the overnight grown bacteria were suspended in 60 μL of an alkaline solvent (0.5 gr SDS and 0.4 gr NaOH dissolved in 200 μL distilled water), then warmed at 95°C for 10 minutes. Next, centrifuged at 13000 rpm for 5 min, and 180 μL distilled water added to the mixture.…”
Section: Genomic Dna Extractionmentioning
confidence: 99%
“…(isolated from soil and drainage water samples collected from three areas in Slovakia that had been industrially polluted with heavy metals) is high and what is more in different species various numbers of genetic orthologs could be observed. These authors suggested that the presence of plasmids is one of the sources of genetic diversity and that frequently, heavy metal resistance in acinetobacters is plasmid encoded [57]. Other researchers also showed multiple plasmids (plasmidome) encoding resistance to Hg, Cr, Co/ Zn/Cd, Ni, and As in Acinetobcter strains and suggested that these plasmidomes can provide resistance to heavy metals in both environmental and clinical habitats [58][59][60].…”
Section: Plos Onementioning
confidence: 98%
“…In our studies, bacterial representatives belonging to Acinetobacter genus seemed to be in seventh position according to their abundance (0.07-4.9%). Šipošová et al [57] showed that genetic variability in Acinetobacter sp. (isolated from soil and drainage water samples collected from three areas in Slovakia that had been industrially polluted with heavy metals) is high and what is more in different species various numbers of genetic orthologs could be observed.…”
Section: Plos Onementioning
confidence: 99%
“…Genes. The alkaline lysis method based on sodium dodecyl sulfate (SDS) (Sigma) and NaOH (Sigma) was used for DNA extraction [16]. Briefly, we solved 0.5 g SDS and 0.4 g NaOH in 200 ml distilled water and suspended the bacterial colony in 20 μl of this extraction buffer.…”
Section: Dna Extraction and Amplification Of Ame-encodingmentioning
confidence: 99%